Konsumsi Kopi Dan Kualitas Tidur Meningkatkan Tekanan Darah Pada Hipertensi di Puskesmas Putri Ayu Kota Jambi Tahun 2021 - Miranda Saraswati; Ani Astuti; Dian Octavia (Universitas Ivet, 2022)
Hypertension is a disease that kills silently, it is necessary to understand the patient in maintaining blood pressure stability, one of which is the risk factor for increasing blood pressure, namely coffee consumption and sleep quality. This study aims to determine the relationship between coffee consumption habits and sleep quality with blood pressure in patients with hypertension. This study is a quantitative study with a cross sectional study design. The population in this study were all hypertensive patients who visited the Putri Ayu Health Center in Jambi City in 2021, totaling 4136 people and sampling was carried out using purposive sampling technique as many as 98 people. Instrument using questionnaires and analysis using univariate and bivariate with chi-square test. The results of univariate analysis showed that 56 (57.1%) respondents had a habit of consuming coffee in the light category, 44 (44.9%) respondents had good sleep quality and 57 (58.2%) respondents had blood pressure. in the category of hypertension grade 1. The results showed that there was a relationship between the habit of consuming coffee (p=0.001) and sleep quality (p=0.031) with blood pressure in patients with hypertension. It can be concluded that coffee consumption and sleep quality can increase blood pressure